Morphological and Mechanical Study of Gelatin/Hydroxyapatite Composite based Scaffolds for Bone Tissue Regeneration - Moh Rifqi Nawafi; Masruroh Masruroh; Dionysius Joseph Djoko Herry Santjojo (Department of Physics, Sebelas Maret University, 2022)
Gelatin-Hydroxyapatite (GHA) composite has been synthesized as a scaffold in bone tissue engineering. The purpose of this study was to find the optimal composition of the GHA scaffold composite which has the best mechanical properties. The independent variable in this study was the composition of HAp. Hydroxyapatite was synthesized by precipitation method from Ca(OH)2 and (NH4)2HPO4 as raw materials. Scaffold from GHA Composite was made by freeze-drying technique with freezing time for 8 hours at -80º C and drying with lyophilizer. The results were characterized using XRD, optical microscopy and tested for compressive strength. The results of the XRD showed that there was no change in a compound or the formation of new bonds on the GHA scaffold when it became a composite which was indicated by the absence of new peaks. It is also known that the peaks decrease in intensity as the amount of polymer in the composite increases. The highest degree of crystallinity was found in the 1:3 GHA sample because it had the highest concentration of HAp. The results of observations with an optical microscope showed that the most homogeneous pore surface morphology was GHA 1:2 with an average pore size of 225.12 ± 16.57 μm. From the results of the compressive strength test, the best value for the 1:2 GHA scaffold was 18.1 ± 0.61 MPa. The values obtained by this scaffold are following the minimum requirements for canceled scaffold so that it can be used as a scaffold candidate in bone tissue engineering.